ВПЛИВ ФІЛЬТРА В КАНАЛІ КЕРУВАННЯ КОНТУРОМ СТАБІЛІЗАЦІЇ НАПРУГИ НАКОПИЧУВАЛЬНОГО КОНДЕНСАТОРА НА ДИНАМІКУ ТРИФАЗНОГО ПАРАЛЕЛЬНОГО АКТИВНОГО ФІЛЬТРА - К.І. Денисенко; В.О. Лесик; Т.В. Мисак (Праці Інституту електродинаміки Національної академії наук України, 2021)
The object of research is a three-phase shunt active power filter, which consists of a semiconductor voltage inverter on fully controllable switches, capacitive storage, and an RL-link. The carried-out decomposition of the research object according to the rate of motion of the dynamic system makes it possible to divide this dynamic system into two subsystems, interconnected by control. The role and influence of the communication subsystem between the voltage stabilization circuit on the storage capacitor of the three-phase shunt active power filter and the circuits for the formation of the compensation current, which is injected by this filter into the distributed power supply network, is considered. The presence of a non-linear load in this network is a source of distortion of the parameters of electrical energy. The formation of the compensation current by the forced introduction of the first order sliding modes along some sliding surfaces was carried out. The two-dimensional sliding surface is a linear combination of the components of the two-dimensional error vectors of the compensation current and the first derivative of the error of this current. The introduced communication subsystem makes it possible to reduce the influence of the disturbance in the form of harmonic components of the rectified voltage on the parameters of the compensating current. The influence of the dynamic characteristics of a communication subsystem with filtering properties on the performance indicators of a parallel active filter and the current distortion factor in the power supply network to which this filter is connected was analyzed. To confirm the theoretical assumptions, a simulation model was built and the results of digital modeling were analyzed. Comparison of different types of filters as a communication subsystem according to the criteria of the duration of the transient process and the harmonic distortion in the current that consumed from the network was carried out. References 26, figures 4, tables 3.